Importazioni di ceramiche fini orientali ad Aquileia. Nuovi dati dalle collezioni storiche del Museo Archeologico Nazionale. II: La ceramica e le lucerne plastiche di produzione cnidia e altre produzioni microasiatiche - Ventura, Paola; Maggi, Paola (Rei Cretariae Romanae Fautorum Acta, 2024)
The thorough examination of fine Oriental ceramics in the historical collections of the National Archaeological Museum of Aquileia, previously conducted regarding Eastern sigillata and Corinthian relief ware in RCRF 46 (Ventura e Maggi 2020), has now been completed. This review encompasses Knidian relief ware, along with other productions from Asia Minor (primarily from Pergamon), and fragments of ceramic lamps from the same region. The pottery collection (51 specimens) comprises both closed forms (such as oinophoroi or other cylindrical jugs, pelikai and amphorae) and open ones (like lagynoi and phialai), as well as a wide array of plastic vessels (including anthropomorphic, zoomorphic and phallic examples). The lamp collection (19 specimens) includes anthropomorphic or zoomorphic lamps in addition to horse’s head ends of the volutes of Broneer XXI lamps and curved handles, sometimes with grooves, terminating in animal heads.